Effects of Minimalist Footwear on Postural Stability, Plantar Footprint, and Safety in Healthy Adults: A Single-Blind Randomized Clinical Trial - Daniel García-García; Rocío Llamas-Ramos; Jorge Juan Alvarado-Omenat; Marta Correyero-León; Inés Llamas-Ramos (Applied Sciences, 2026)
This study evaluated the long-term changes induced by wearing minimalist footwear (MF) during activities of daily living (ADLs) on the plantar footprint and postural stability in healthy adults. In this randomized clinical trial, a total of 95 healthy adults were recruited; 90 participants completed the protocol and were analyzed in either an experimental group (EG, n = 45), which wore MF for at least 5 h per day over a 6-month period, or a passive control group (CG, n = 45). Plantar pressure distribution (forefoot, rearfoot, and total contact areas), static stability (center of pressure (CoP) displacement under open-eyes and closed-eyes conditions), and dynamic stability (forward reach test) were assessed using a force platform at baseline and post-intervention. A self-reported questionnaire and an adverse event record were also completed by the EG. Statistical analysis was carried out using a repeated-measures analysis of variance (ANOVA) and a paired Student’s t-test; statistical significance level was set at p < 0.05. The Group